The project of “social theology” in the teachings of Walter Rauschenbusch - Ekaterina Khitruk (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия)
The article examines the question of the possibility of transforming systematic theology in accordance with the main ideas of the "social gospel". This question was formulated in the last significant work of the eminent American theologian of the early twentieth century, Walter Rauschenbusch, Theology for the Social Gospel. The work was published in 1917, a year before the thinker's death. Walter Rauschenbusch was convinced that it was necessary to transform a number of provisions of Christian doctrine, taking into account some important discoveries that became apparent in the context of the social interpretation of Christianity. These "discoveries" seem new only from the standpoint of historical Christianity, which was seriously influenced by the mystical, metaphysical and ascetic tendencies of the Greco-Roman intellectual tradition alien to it. In reality, according to V. Raushenbush, these “discoveries” of the social gospel were part of the original content of the Christian gospel and are now again updated in the context of social interpretation. W. Rauschenbusch refers to such provisions of the social gospel, which should be introduced into systematic Christian theology, the following ideas: 1. A broader interpretation of the nature of evil (evil has not only an individual, but also a social nature). Evil is rooted not only in a person's freedom, but also in some social institutions that incline a person's will to a vicious life. 2. “Limiting the theological weight” of the doctrine of the original sin in order to educate Christians in active enthusiasm instead of passive contrition for the fall, the consequences of which no one can overcome. 3. Salvation has both a personal and a social dimension. The personal conversion of a Christian is necessarily linked to his social mission. Social responsibility should not be seen as a secondary consequence of acquiring personal faith. One is unthinkable without the other. By acquiring personal faith, a person also acquires social responsibility towards other people. 4. Democratic character of theology instead of despotic. Theology should be guided by the gospel understanding of God as a loving and merciful Father. 5. Social interpretation of eschatology. The posthumous existence of people in heaven and hell should not be regarded as a state of "eternal rest". It is necessary to admit the existence of active love in paradise, which will contribute to the correction of sinners and the perfection of the righteous. It is an eschatology of hope instead of an eschatology of punishment.